2020
DOI: 10.1093/jamia/ocaa099
|View full text |Cite
|
Sign up to set email alerts
|

Integrated displays to improve chronic disease management in ambulatory care: A SMART on FHIR application informed by mixed-methods user testing

Abstract: Objective The study sought to evaluate a novel electronic health record (EHR) add-on application for chronic disease management that uses an integrated display to decrease user cognitive load, improve efficiency, and support clinical decision making. Materials and Methods We designed a chronic disease management application using the technology framework known as SMART on FHIR (Substitutable Medical Applications and Reusable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 33 publications
0
31
1
Order By: Relevance
“…Outcomes: An experimental simulation study of this tool for COPD management found that compared to the EHR alone, the app was associated with improved completion of recommended care (81% vs. 48%, P < 0.001), reduced time spent per task, and reduced user frustration. 59 A clinical trial is underway.…”
Section: Resultsmentioning
confidence: 99%
“…Outcomes: An experimental simulation study of this tool for COPD management found that compared to the EHR alone, the app was associated with improved completion of recommended care (81% vs. 48%, P < 0.001), reduced time spent per task, and reduced user frustration. 59 A clinical trial is underway.…”
Section: Resultsmentioning
confidence: 99%
“…The most common study design was observational (n=8; 67%), with three studies (25%) reporting CDS needs evaluations. We identified only two studies with randomized components reporting on the use of any of the standards of interest (Curran et al [ 27 ] and Kawamoto et al [ 28 ]). Two (17%) articles reporting evaluations were in the design stage, seven (58%) were in the piloting stage, and a further three (25%) were deployed in real clinical settings.…”
Section: Resultsmentioning
confidence: 99%
“…For example, we searched only one database, our search strategy was not developed with assistance from an expert librarian, and the data analysis did not follow standard scoping review methods. As another limitation, the study was conducted over a short period in which we observed rapid development of the literature; the most recent article captured in the search was published in August, 2020 [ 27 ]. It is highly likely that new studies have been published that were not captured in our October 21, 2020 literature search at the time of writing.…”
Section: Discussionmentioning
confidence: 99%
“…Other strategies should include eHealth literacy programs that address patients’ concerns regarding safeguarding their protected health information. Additional technological improvements may include the use of integrated displays to decrease user cognitive load [ 49 , 50 , 51 ], integration of linked EHR records at the household level to facilitate delivery of services, and embedding of health literacy tools (e.g., embedded medical search engines, integrated AI voice chatbots for on-demand self-care advice) to facilitate meaningful patient engagement.…”
Section: Discussionmentioning
confidence: 99%